EFFICIENCY OF INDIAN STOCK MARKET- A STUDY OF EXISTENCE OF ARBITRAGE GAINS THROUGH PUT CALL PARITY (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2022)
Put call parity is the no arbitrage condition  which must hold true for an efficient financial  market. The present study examines the Indian  stock market efficiency by using different option  contracts for about 400 observations during  three consecutive months. Deviation in PCP  model provides opportunity to earn abnormal  profits to arbitrageur. Three different scenarios  have been considered for testing the PCP model.  Our result in all scenarios shows the mispricing  in the Indian stock market. The empirical  analysis provides the level of profit which can  be made by arbitrageur. The findings show that  Indian stock market as inefficient market.
Keywords: Put Call parity; Market efficiency; Arbitrage profit